Risk Factors for Readmission After Cleft Lip Repair. Issue 7 (October 2019) - Chouairi, Fouad; Mercier, Michael R.; Mets, Elbert J.; Alperovich, Michael
Abstract : Background: Cleft lip is the most common craniofacial malformation with an incidence of 1 in 700 live births. Our study sought to evaluate incidences and risk factors readmission following CLP repair using a well-validated national surgical database. Methods: All cleft lip repairs performed between 2012 and 2016 were identified in the American College of Surgeons National Surgical Quality Improvement Program Pediatric Database. Patient demographics, surgical variables, and reasons for readmission were analyzed and identified. A binary logistic regression was performed to identify factors independently associated with readmission following cleft lip repair. Results: The 4550 cleft lip repairs were identified with a thirty-day readmission rate of 3.8% (173 patients). A higher incidence of readmission was identified among patients with developmental delay ( P ⩽0.001), seizure disorder ( P <0.001), structural central nervous system abnormality ( P ⩽0.001), steroid use within 30 days ( P ⩽0.001), a requirement for nutritional support ( P <0.001), and ASA of 3 or higher (17.3% vs 9.9%, P <0.001). Readmitted patients were more likely to have deep incisional surgical site infections ( P <0.001), deep wound dehiscence ( P = 0.002), reoperation ( P <0.001), pneumonia ( P <0.001), and unplanned intubation ( P <0.001). Multivariate regression identified seizure disorder (OR = 3.3; 95% CI = 1.3–8.3; P = 0.012) and steroid use within 30 days (OR = 3.8; 95% CI = 1.1–12.2; P = 0.030) as independently associated with readmission. The mean time of readmission was 9 days after operation. Conclusion: Patients with seizure disorder and steroid use were significantly more likely to be readmitted. Physicians should be cautious with management of patients with these risk factors. Abstract : Supplemental Digital Content is available in the text